PERCEPTIONS OF PRIMARY HEALTH CARE (PHC) DOCTORS ON THE PREVENTION OF CORONARY HEART DISEASE (CHD) IN RIYADH, SAUDI ARABIA - Al-Shehri, Ali M. (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: Coronary heart disease (CHD) is the leading cause of death throughout the world. PHC doctors are in a unique position to prevent CHD and promote health in the population. However, the perception of PHC doctors on CHD prevention has not been well documented. OBJECTIVES: To explore and examine the perception of PHC doctors on the prevention of CHD. Subject and method: A questionnaire survey of all PHC doctors attending a continuing medical education (CME) activity in Riyadh city. The questionnaire was designed and piloted with local PHC doctors before being used in this survey. RESULTS: All the 77 PHC doctors responded (100%) and almost all the them (97.4%) agreed that the primary prevention of CHD was an essential task. Fifty-two participants (67.53%) confirmed that little attention had been paid to the primary prevention of CHD. While the majority of respondents (71.43%) felt that the primary prevention of CHD was an easy task, a significant minority (23.37%) disagreed. Interestingly, 70 (90.91%) respondents were not aware of any local literature on how to achieve primary prevention of CHD and would like to have the literature made available to them. Finally, participants indicated that the percentage prevalence of CHD risk factors among their patients was high. CONCLUSION: the findings of this survey confirm a general feeling that the primary prevention of CHD is not being given enough attention. Participants accepted that the primary prevention of CHD was an essential part of their work, but the lack of local literature and research on this vital area was a major concern.